Adaptive PID control via sliding mode for position tracking of quadrotor MAV: Simulation and real-time experiment evaluation - Mohd Basri, Mohd Ariffanan; Noordin, Aminurrashid; Mohamed, Zaharuddin (MDPI, 2023)
The lightweight nature of micro air vehicles (MAVs) makes them highly sensitive to perturbations, thus emphasizing the need for effective control strategies that can sustain attitude stability throughout translational movement. This study evaluates the performance of two controllers (Proportional-Integral-Derivative (PID) and Adaptive PID based on Sliding Mode Control (SMC)) on a MAV that is subjected to external disturbances. These controllers are initially simulated using MATLAB®/Simulink™ and then implemented in real-time on the Parrot Mambo Minidrone. The observation on the waypoint follower and the orbit follower in both simulation and experiment showed that the Adaptive PID (APID) controller is more effective and robust than the PID controller against external disturbances such as wind gusts. The study provides evidence of the potential of the APID control scheme in enhancing the resilience and stability of MAVs, making them suitable for various applications including surveillance, search and rescue, and environmental monitoring.